Heart transplantation outcomes for rheumatic heart disease: Analysis of international registry data. Issue 12 (22nd November 2018) - Dan, Jennifer M.; Silva Enciso, Jorge; Lund, Lars H.; Aslam, Saima
Abstract: Background: Rheumatic heart disease (RHD), an autoimmune sequela of Group A streptococcal infection, is a chronic valvular disease affecting 32 million people worldwide, predominantly in developing nations. As the predisposition to autoimmune sequela still remains post transplantation, our primary objective was to assess if there were differences in mortality and rejection rates. Methods and Results: Using the International Society for Heart and Lung Transplantation (ISHLT) adult heart transplant registry, we identified 42 RHD patients who had undergone heart transplantation between 1988 and 2014. We matched the 42 RHD recipients by transplant year, age, and gender to 420 dilated cardiomyopathy (DCM) recipients. One‐year mortality in the RHD group was 17.95% vs. 7.92% in the DCM group ( P  = 0.07). Survival was significantly reduced in the RHD group vs. the DCM group via Kaplan Meier curves ( P  = 0.04). In a multivariate model, RHD status (OR 3.19, 95% CI 1.15‐8.83, P  = 0.025) and serum creatinine (OR 1.41, 95% CI 1.09‐1.82, P  = 0.009) were associated with an increased odds of one‐year mortality ( P  = 0.0013). Conclusions: At one year post transplantation, RHD recipients had a significantly lower survival than DCM recipients. RHD status was also an independent predictor of mortality at 1 year post transplantation.